P37 BTK inhibitor Ibrutinib regulates the TLR3 induced IL-1ß expression in HNSCC. Issue 5 (May 2015) - Lanka, A.; Pries, R.; Wollenberg, B.
<x xml:space="preserve">Abstract</x> Introduction Ibrutinib is the first drug designed to inhibit Burton's tyrosine kinase (BTK) activity. It is a new targeted therapy for chronic lymphocytic leukemia (CLL). BTK plays a critical role in humoral immune responses and is essential mediator for the growth and survival of B-Cells. Several unknown underlying immunosuppressive mechanisms are involved in the development of Head and Neck Squamous Cell Carcinomas (HNSCCs) worldwide. Material and methods To investigate how the BTK inhibitor Ibrutinib influences the progression and microenvironment biosynthesis in HNSCC, different established HNSCC cell lines were treated with Ibrutinib and triggered with the TLR3 ligand Polyinosinic:polycytidylic acid (PolyI:C) through both extracellular and intracellular ways. Results This resulted in reduced expression levels of immunomodulatory cytokines IL-1<alternatives><inline-graphic xlink:href="ark:/27927/pgjcwgwr0b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> and IL-8. Furthermore, our data demonstrate an efficient suppression of the extracellular-signal regulated kinase1/2 (ERK1/2) MAPK as well as significantly reduced cell viability. Conclusion Therefore, Ibrutinib could be a new and promising approach to unfold the underlying immunosuppressive mechanisms involved in HNSCC.